2020
DOI: 10.1007/s00044-020-02591-8
|View full text |Cite
|
Sign up to set email alerts
|

Ester and amide derivatives of rhodamine B exert cytotoxic effects on different human tumor cell lines

Abstract: Three esters of rhodamine B (1–3) differing in their alkyl chain lengths as well as several rhodamine B amides (4–9) were synthesized in good yields and tested for their cytotoxicity in SRB assays employing several human tumor cell lines. The rhodamine B esters were unselective but showed cytotoxicity of as low as EC50 = 0.15 ± 0.02 µM. The rhodamine B amides were slightly less cytotoxic but showed good selectivity against MCF-7 and A2780 tumor cell lines. Especially a morpholinyl derivative 4 was ~20 time mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The triterpenoid skeleton is equally important. Here, too, it was shown that "simple" RhoB conjugates 1-9 ( Figure 3) also had lower cytotoxicity than the corresponding triterpenoid analogs, but their tumor cell/non-tumor cell selectivity was also diminished (Table 1) [91]. Of special interest seems the morpholinyl derivative 4 inasmuch as this compound held the highest selectivity of this series with respect to MCF-7 carcinoma cells (S = (EC 50, NIH 3T3 / EC 50, MCF-7 ) > 19.5) and A2780 ovarian cancer cells (S = (EC 50, NIH 3T3 / EC 50, A27807 ) > 18.1) [90].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The triterpenoid skeleton is equally important. Here, too, it was shown that "simple" RhoB conjugates 1-9 ( Figure 3) also had lower cytotoxicity than the corresponding triterpenoid analogs, but their tumor cell/non-tumor cell selectivity was also diminished (Table 1) [91]. Of special interest seems the morpholinyl derivative 4 inasmuch as this compound held the highest selectivity of this series with respect to MCF-7 carcinoma cells (S = (EC 50, NIH 3T3 / EC 50, MCF-7 ) > 19.5) and A2780 ovarian cancer cells (S = (EC 50, NIH 3T3 / EC 50, A27807 ) > 18.1) [90].…”
Section: Resultsmentioning
confidence: 94%
“…The triterpenoid skeleton is equally important. Here, too, it was shown that “simple” RhoB conjugates 1 – 9 ( Figure 3 ) also had lower cytotoxicity than the corresponding triterpenoid analogs, but their tumor cell/non-tumor cell selectivity was also diminished ( Table 1 ) [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…While some specific palladium-based Pd 2 L 4 nanospheres are highly toxic, 14,28–30 other structures, especially with similar design to our framework have shown little toxicity. 12,15,31 Recent studies revealed the high toxicity of rhodamine derivatives, 37,38 making our systems, with the well-defined nanosphere and linked toxic units, interesting candidates for structure-cytotoxicity assays. We anticipate differences between the molecular building blocks and their nanosphere analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Next to the required spectroscopic features for in vivo detection, rhodamine B amide derivatives have shown recently potent cytotoxicity against different human cancer types. 37,38 Furthermore, singlet oxygen formation using rhodamine dyes emerged as a tool in photodynamic therapy of tumor cells. 39,40 Therefore, rhodamine functionalization of nanospheres can yield systems which are not only suitable for in vivo imaging, but also can have cytotoxic properties by themselves or through light driven singlet oxygen ( 1 O 2 ) formation.…”
Section: Ligand Design and Nanosphere Synthesismentioning
confidence: 99%
See 1 more Smart Citation